Tafsir Historis Kristis terhadap 1 Petrus 5: 1-11 - Friska Deniwaty Pasaribu; Fritcen Vanny M. Pardede; Destana S.R. Banurea (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This research examines debates among the early congregation regarding Jewish religious morality and ceremonies and their implications in the context of contemporary church pastoring. Through a critical historical exegesis approach and literature study, this article explores the views of Paul and Peter regarding the application of Torah law to Gentile Christians. This research highlights that a pastor must be an example for the congregation, not rule arbitrarily, and remain focused on God's call in their ministry. Analysis of the social, economic, and cultural context of the time this letter was written also provides insight into the challenges the early congregation faced. The relevance of this research lies in the application of pastoral principles in today's church ministry, which demands humility and example from church leaders.